Tomato Cultivars With Variable Tolerances to Water Deficit Differentially Modulate the Composition and Interaction Patterns of Their Rhizosphere Microbial Communities - Gaete, Alexis; Pulgar, Rodrigo; Hodar, Christian; Maldonado, Jonathan; Pavez, Leonardo; Zamorano, Denisse; Pastenes, Claudio; González, Mauricio; Franck, Nicolás; Mandakovic, Dinka (Frontiers in Plant Science, 2021)
Since drought is the leading environmental factor limiting crop productivity and plants have a significant impact in defining the assembly of plant-specific microbial communities associated with the roots, we aimed to determine the effect of thoroughly selected water deficit tolerant and susceptible Solanum lycopersicum cultivars on their rhizosphere microbiome and compared their response with plant-free soil microbial communities. We identified a total of 4,248 bacterial and 276 fungal different OTUs in the soils by massive sequencing. We observed that tomato cultivars significantly affected the alpha and beta diversity of their bacterial rhizosphere communities but not on their fungal communities compared to bulk soils (BS), showing a plant effect exclusively over the bacterial soil community. Also, an increase in alpha diversity in response to water deficit of both bacteria and fungi was observed in the susceptible (SRz) rhizosphere but not in the tolerant (TRz) cultivar, implying a buffering effect of the tolerant cultivar over its rhizosphere microbial communities. Even though water deficit did not affect the tolerant cultivar's microbial diversity, our interaction network analysis revealed that the TRz microbiota displayed the smallest and least complex soil network in response to water deficit with the least number of connected components, nodes, and edges. This reduction of the TRz network also correlated with a more efficient community, reflected in increased cooperation within kingdoms. Furthermore, we identified some specific bacteria and fungi in the TRz in response to water deficit, which, given that they belong to taxa with known beneficial characteristics for plants, could be contributing to the tolerant phenotype, highlighting the metabolic bidirectionality of the holobiont system. Futures assays involving the characterization of root exudates and the exchange of rhizospheres between drought-tolerant and susceptible cultivars could determine the effect of specific metabolites on the microbiome community and may elucidate their functional contribution to the tolerance of plants to water deficit.